2021
DOI: 10.1186/s12935-021-02266-3
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis combined with experiments predicts CTHRC1 as a therapeutic target for human cancers

Abstract: Background The function of collagen triple helix repeat containing 1 (CTHRC1) as an oncogene has been reported in a growing number of publications. Bioinformatics methods represent a beneficial approach to examine the mechanism and function of the CTHRC1 gene in the disease process of cancers from a pan-cancer perspective. Methods In this study, using the online databases UCSC, NCBI, HPA, TIMER2, Oncomine, GEPIA, UALCAN, cBioPortal, COSMIC, MEXPRES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The Human Protein Atlas (HPA) online website ( ) was used to analyze ALKBH5 in “Tissue Atlas”. The expression data of ALKBH5 gene in different human normal tissues were obtained ( 24 ). The row data source was TMM normalized.…”
Section: Methodsmentioning
confidence: 99%
“…The Human Protein Atlas (HPA) online website ( ) was used to analyze ALKBH5 in “Tissue Atlas”. The expression data of ALKBH5 gene in different human normal tissues were obtained ( 24 ). The row data source was TMM normalized.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies showed that CTHRC1 was overexpressed in various cancer types and functions as an important oncogene that may promote tumorigenesis and development through different mechanisms including glioma [ 23 ]. Analysis of CTHRC1 expression in 41 glioma samples confirmed these results (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These studies have specifically implicated CTHRC1 with immune infiltration in Kidney and Brain cancers. Peng at al [ 38 ] reported that in addition to being upregulated in high-grade gliomas, CTHRC1 expression correlated with genes associated with the Wnt Signaling pathway (DVL3, DVL1, DVL2, ROR2, WNT3A, FZD6 and FZD5). Our study in evaluating 1027 matrisome genes across cancers, has identified a novel set of genes (MMP13, FNDC1, SFRP4 and ADAMTS16) that could work with CTHRC1 to regulate cancer progression.…”
Section: Discussionmentioning
confidence: 99%